2022
DOI: 10.1097/mat.0000000000001832
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Lower Extremity Ischemia on Femoral Veno-Arterial Extracorporeal Membrane Oxygenation

Abstract: Ipsilateral lower extremity ischemia is a common and morbid complication during veno-arterial extracorporeal membrane oxygenation (VA-ECMO). The cannula can impede ipsilateral distal arterial flow leading to critical limb ischemia. Cannula size, placement, and utilization of distal perfusion catheters are strategies that have been used to prevent this complication. We report the novel case of a 19-year-old female on VA-ECMO complicated by contralateral lower extremity ischemia. Diagnosis was made by computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A prospective trial found an incidence of critical limb ischemia of 38% in patients with refractory cardiogenic shock supported with VA-ECMO [ 19 ]. ALI can lead to further complications and negatively affect patients’ survival [ 3 ]. The use of a DPC aims at avoiding ALI, but its efficiency has not yet been proven, and up to 26% of patients under VA-ECMO experience ALI despite the use of a DPC [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective trial found an incidence of critical limb ischemia of 38% in patients with refractory cardiogenic shock supported with VA-ECMO [ 19 ]. ALI can lead to further complications and negatively affect patients’ survival [ 3 ]. The use of a DPC aims at avoiding ALI, but its efficiency has not yet been proven, and up to 26% of patients under VA-ECMO experience ALI despite the use of a DPC [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ipsilateral ALI occurs in 11 to 52% of VA-ECMO cases and can lead to further complications, including compartment syndrome requiring fasciotomy, functional deficit, or amputation of the lower limb. ALI carries a higher risk of a lethal outcome than other complications of VA-ECMO [ 3 ]. The burden of ALI might even counterbalance the physiological benefit of ECMO and hinder the survival benefit of this technique [ 4 ].…”
Section: Introductionmentioning
confidence: 99%